Fingerprint Pre-processing on ARM and DSP Platforms - Gok, M.; Gorgunoglu, S.; Muharrem Orak, I. (Elektronika ir Elektrotechnika, 2014)
In minutiae based fingerprint analysis, fingerprint image is pre-processed before extracting features. The pre-processing is carried out to obtain more accurate minutiae points. Implementing fingerprint programs on embedded systems can be considered as important especially for real time standalone applications. Reducing the pre-processing time is important for identification and verification in real time embedded systems. In this study, pre-processing of minutiae based fingerprint system is implemented on two different platforms: Texas Instruments Sitara AM3359 which is a single board computer and OMAP-L138 which is a development kit. OMAP-L138 is a low power application processor based on ARM9 and C674x DSP cores. AM3359 is microprocessor unit based on ARM Cortex-A8 core. Fingerprint pre-processing algorithms are implemented using C/C++ compiler and tested on three different cores: ARM9, DSP and ARM Cortex-A8. The execution times are compared with each other. The results show that using DSP core, execution time is substantially improved. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.7287